2015
DOI: 10.1186/1471-2164-16-s7-s15
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis profiles metabolic pathways in traditional herb Astragalus membranaceus Bge. var. mongolicus (Bge.) Hsiao

Abstract: BackgroundAstragalus membranaceus Bge. var. mongolicus (Bge.) Hsiao (A. mongolicus, family Leguminosae) is one of the most important traditional Chinese herbs. Among many secondary metabolites it produces, the effective bioactive constituents include isoflavonoids and triterpene saponins. The genomic resources regarding the biosynthesis of these metabolites in A. mongolicus are limited. Although roots are the primary material harvested for medical use, the biosynthesis of the bioactive compounds and its regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 70 publications
4
24
0
Order By: Relevance
“…In present study, multiple transcripts which encoded some of the known enzymes participated in the MVA pathway and the saponin biosynthesis pathway were found in traditional herbs, e.g., Panax ginseng (Cao et al, 2015), Phyllanthus amarus (Mazumdar and Chattopadhyay, 2016), Panax japonicus (Rai et al, 2016), Astragalus membranaceus Bge (Chen et al, 2015), and Eleutherococcus senticosus (Hwang et al, 2015). Genes involved in the MVA pathway in the A. bidentata transcriptome included 3-hydroxy-3-methylglutaryl CoA synthase (HMGS), HMG-CoA reductase (HMGR), phosphomevalonate kinase (PMK), mevalonate-5-diphosphate decarboxylase (MDD), isopentenyl diphosphate isomerase (IDI), geranyl diphosphate synthase (GPPS), farnesyl diphosphate synthase (FPS), geranylgeranyl diphosphate synthase (GGPPS), squalene synthase (SS), squalene epoxidase(SE), beta-amyrin synthase (β-AS), and CAS.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…In present study, multiple transcripts which encoded some of the known enzymes participated in the MVA pathway and the saponin biosynthesis pathway were found in traditional herbs, e.g., Panax ginseng (Cao et al, 2015), Phyllanthus amarus (Mazumdar and Chattopadhyay, 2016), Panax japonicus (Rai et al, 2016), Astragalus membranaceus Bge (Chen et al, 2015), and Eleutherococcus senticosus (Hwang et al, 2015). Genes involved in the MVA pathway in the A. bidentata transcriptome included 3-hydroxy-3-methylglutaryl CoA synthase (HMGS), HMG-CoA reductase (HMGR), phosphomevalonate kinase (PMK), mevalonate-5-diphosphate decarboxylase (MDD), isopentenyl diphosphate isomerase (IDI), geranyl diphosphate synthase (GPPS), farnesyl diphosphate synthase (FPS), geranylgeranyl diphosphate synthase (GGPPS), squalene synthase (SS), squalene epoxidase(SE), beta-amyrin synthase (β-AS), and CAS.…”
Section: Resultsmentioning
confidence: 77%
“…Most of the genes involved in triterpene saponins biosynthesis showed higher expression in root tissues compared with leaf tissues ( Figure 8 ). Additionally, more experiments showed that genes involved in pathway of saponion biosynthesis displayed similar expression pattern in Panax japonicus (Rai et al, 2016), and Astragalus membranaceus Bge (Chen et al, 2015). However, the CAS gene was significantly down-regulated in root tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high throughput transcriptome sequencing and analyses have become a versatile method for gene discovery and expression profiling in recent years (Kalra et al, 2013; Chen et al, 2015). The Illumina sequencing technology has proven to be an exceptionally successful in a wide variety of whole-transcriptome investigations, particularly for the characterization of non-model organisms where reference genome is not available (Wilhelm et al, 2008; Tang et al, 2011; Chen et al, 2015; Kumar S. et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Illumina sequencing technology has proven to be an exceptionally successful in a wide variety of whole-transcriptome investigations, particularly for the characterization of non-model organisms where reference genome is not available (Wilhelm et al, 2008; Tang et al, 2011; Chen et al, 2015; Kumar S. et al, 2015). Several computational tools for de novo assembly of short read sequence data and identification of genes involved in various metabolic pathways have also been demonstrated (Pertea et al, 2003; Zerbino and Birney, 2008; Grabherr et al, 2011; Fu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%